Perbandingan Pegadaian Konvensional dan Pegadaian Syariah dalam Perspektif Hukum Ekonomi Islam - Nadia Rahmadani; Restiani Putri Agustin; Risca Ayu Sabella (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study compares conventional and Islamic pawnshops from the perspective of Islamic Economic Law. Utilizing a qualitative descriptive approach, data were collected through literature reviews and interviews with practitioners. The findings indicate that Islamic pawnshops employ contracts such as rahn, ijarah, and qardh, aligning with Islamic jurisprudence, whereas conventional pawnshops operate based on interest-bearing loans. The study underscores the importance of promoting sharia-compliant financial services to ensure fairness and justice in economic transactions.